Factors Associated with Poor Asthma Control in Children Aged Five to 13 years. Issue 1 (2006) - Mcghan, SL; MacDonald, C; James, DE; Naidu, P; Wong, E; Sharpe, H; Hessel, PA; Befus, AD
Abstract : BACKGROUND: Most children with asthma should be able to achieve acceptable control. However, are there differences between those with acceptable and poor control, and if so, how can health care approaches be modified accordingly? OBJECTIVE: To examine the characteristics of elementary school children aged five to 13 years with acceptable and poor levels of asthma control. METHODS: The present cross-sectional study of children with asthma used five indicators of control, as outlined by the Canadian Asthma Consensus Report, to categorize acceptable and poor asthma control. RESULTS: Of 153 children, 115 (75%) were rated as having poorly controlled asthma. Of those with poor control, 65 (64%) children were currently using inhaled corticosteroids, and 65% of those reported using inhaled corticosteroids daily versus as needed. Fifty-one per cent of the children with poorly controlled asthma had exposure to tobacco smoke, whereas 79% of the children with asthma under acceptable control were from households with no smokers (P=0.002). The poor control group also had significantly worse parental perceptions of the psychosocial impact of asthma on their child. No significant difference was found in the percentage of those who had written action plans in the poor control group (28%) compared with the acceptable control group (26%), and similar percentages in each group stated that they used the plans. CONCLUSIONS: Despite the high use of inhaled corticosteroids, the majority of children had poorly controlled asthma. The poor control group had more exposure to tobacco smoke and a worse psychosocial impact due to asthma. Few children had past asthma education and action plans, suggesting that there is a need to improve access to and tools for education.